1999
DOI: 10.3168/jds.s0022-0302(99)75281-1
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of Yogurt Containing Lactobacillus acidophilus and Bifidobacterium to Potentiate Immunoglobulin A Responses to Cholera Toxin in Mice

Abstract: Lactic acid bacteria have been reported to have benefits for the prevention and treatment of some forms of diarrhea and related conditions. To determine whether these effects might involve direct stimulation of the gastrointestinal immune response, we administered yogurt to try to enhance mucosal and systemic antibodies against an orally presented immunogen, cholera toxin. Yogurts were manufactured with starter cultures containing different species and strains of lactic acid bacteria. Mice were fed these yogur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 32 publications
3
42
0
3
Order By: Relevance
“…Enhancement of the amount of IgA-producing plasma cells by Lactobacillus casei or L. acidophilus has been reported (23). In addition, Tejada-Simon et al (24) showed increased IgA production in response to cholera toxin in mice treated with a yogurt containing a mixture of L. acidophilus and Bifidobacterium spp. On the other hand, studies associating the administration of non-pathogenic E. coli with the induction of antibody responses are rare and the results sometimes controversial.…”
Section: Discussionmentioning
confidence: 96%
“…Enhancement of the amount of IgA-producing plasma cells by Lactobacillus casei or L. acidophilus has been reported (23). In addition, Tejada-Simon et al (24) showed increased IgA production in response to cholera toxin in mice treated with a yogurt containing a mixture of L. acidophilus and Bifidobacterium spp. On the other hand, studies associating the administration of non-pathogenic E. coli with the induction of antibody responses are rare and the results sometimes controversial.…”
Section: Discussionmentioning
confidence: 96%
“…casei and Lb. acidophilus increased IgM forming cell in spleen [7,8]. B. breve strain yakult and Lb.…”
Section: Introductionmentioning
confidence: 96%
“…Many health benefits have been reported, such as immunomodulating effect which helps persons' immunity in retarding number of diseases [6][7][8], reduction of serum cholesterol [9,10], enhancing body absorption of minerals and many other health benefits. However, types of health benefits as well as their mechanisms are microorganism (type & strain) and dose dependent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A utilização conjunta de L. acidophilus e Bifidobacterium spp. tem sido estudada em leites e bebidas fermentadas [15,44], iogurtes comerciais [39] e vários tipos de queijos [29]. Dentre eles, destaca-se o queijo fresco [1,6,7,28,29,31,42].…”
Section: -Introduçãounclassified